THE EFFECTS OF DISTRIBUTED LEADERSHIP ON TEACHERS’ COLLECTIVE EFFICACY AND PROFESSIONAL LEARNING COMMUNITY - Jamil , Mohd Fadzil; Mohd Hamzah , Mohd Izham (International Journal of Educational Best Practices, 2019)
Distributed leadership offers a new-thinking in transforming the school's leadership. Teachers' collective efficacy and professional learning community have been identified to have a strong influence on improving the teaching quality of teachers. This article examines the effects of distributed leadership of secondary school administrators on teacher collective efficacy and professional learning community. The literature suggests that distributed leadership perspective is a good alternative strategy to improve the quality of educational institutions, but empirical evidence showing the effects of distributed leadership on teachers’ collective efficacy and professional learning community that can improve the quality of teacher’s teaching is limited. Data were collected from 592 teachers working in secondary schools in Negeri Sembilan, Malaysia. Distributed leadership of secondary school administrators were determined with Distributed Leadership Inventory developed by Hulpia (2009) while teachers’ collective efficacy was determined using the Collective Efficacy Scales developed by Goddard and Hoy (2003) and professional learning community was determined with the School Professional Staff as Learning Community Questionnaire developed by Hord (1996). Data analysis was done based on Structural Equation Modeling using AMOS software. Regression weight, variance and squared multiple correlations tests were used in data analysis. In conclusion, a strong positive relationship was revealed between distributed leadership of secondary school administrators on teachers’ collective efficacy and professional learning community. Distributed leadership of secondary school administrators was also a significant predictor of teachers’ collective efficacy and professional learning community.